Zebrafish Fins as a Model System for Skeletal Human Studies - Manuel Marí-Beffa; Jesús A. Santamaría; Carmen Murciano; Leonor Santos-Ruiz; José A. Andrades; Enrique Guerado; José Becerra (The Scientific World Journal)
Recent studies on the morphogenesis of the fins of Danio rerio (zebrafish) during development and regeneration suggest that a number of inductive signals involved in the process are similar to some of those that affect bone and cartilage differentiation in mammals and humans. Akimenko et al. (2002) has shown that bone morphogenetic protein-2b (BMP2b) is involved in the induction of dermal bone differentiation during fin regeneration. Many other groups have also shown that molecules from the transforming growth factor-beta superfamily (TGFβ), including BMP2, are effective in promoting chondrogenesis and osteogenesis in vivo in higher vertebrates, including humans. In the present study, we review the state of the art of this topic by a comparative analysis of skeletal tissue development, regeneration and renewal processes in tetrapods, and fin regeneration in fishes. A general conclusion of this study states that lepidotrichia is a special skeletal tissue different to cartilage, bone, enamel, or dentine in fishes, according to its extracellular matrix (ECM) composition. However, the empirical analysis of inducing signals of skeletal tissues in fishes and tetrapods suggests that lepidotrichia is different to any responding features with main skeletal tissues. A number of new inductive molecules are arising from fin development and regeneration studies that might establish an empirical basis for further molecular approaches to mammal skeletal tissues differentiation. Despite the tissue dissimilarity, this empirical evidence might finally lead to clinical applications to skeletal disorders in humans.